Association of physician-diagnosed asthma and household indoor air pollution among school children in three urban centers in the Philippines a case control study. - Sto. Niño, Oscar Vic B.
Childhood asthma is an emerging chronic disease that significantly burdens the child, family and society. Although the etiology of childhood asthma remains unclear, it is usually caused by the child's genetic predisposition and environmental exposures. Use of solid fuels (USF) and environmental tobacco smoke (ETS) are the major sources of indoor air pollution that trigger asthma among children. This study aimed to determine the associations of USF and ETS in the household with physician-diagnosed asthma among schoolchildren aged 13-14 years. It also aimed to determine whether sex, family history (FHX) of asthma and socioeconomic status (SES) significantly confound these associations. The study utilized a case-control design with prevalent cases from the National Asthma Epidemiology Study (2002). Principal component analysis was done to derive a more reliable indicator for SES. Bayesian logistic regression analysis was performed to incorporate prior information and provide straightforward interpretations about the parameter estimates. Nine hundred sixty-two (962) schoolchildren were included, 208 (22%) were definite asthmatics and 754 (78%) were definite non-asthmatics. The prevalence odds of childhood asthma were 1.6 times higher when exposed to ETS (credible interval (Crl): 1.25-2.05) and only 1.2 times higher when exposed to USF (90% Crl: 0.94-1.48). SES distorts the association of asthma with ETS and USF by 6% toward the null. Asthma FHX distorts the association of ETS and asthma by 10% away from the null. Exposure to ETS is associated with childhood asthma (odds ratio (OR): 1.6, 90% Crl: 1.25-2.05) but not exposure to USF (OR: 1.19, 90% Crl: 0.94-1.48). SES confounds the association of childhood asthma and both exposures to ETS and USF. Asthma FHX confounds the association of childhood asthma and exposure only to ETS.